An algorithm for the numbers of endomorphisms on paths (DM13208) - Sr Arworn (2018)
An endomorphism of a graph is a mapping on the vertex set of the graph which preserves edges. In this paper we provide an algorithm to determine the cardinalities of endomorphism monoids of finite undirected paths. © 2008 Elsevier B.V. All rights reserved.